2020
DOI: 10.1080/21691401.2020.1725536
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA cZNF292 silence alleviates OGD/R-induced injury through up-regulation of miR-22 in rat neural stem cells (NSCs)

Abstract: Background: Hypoxic-ischaemic encephalopathy (HIE) is a prevailing severe brain damage disease in newborns, and caused by perinatal asphyxia cerebral ischaemia and reperfusion. Here, we investigated the role of cZNF292 in oxygen-glucose deprivation/reperfusion (OGD/R)-induced neural stem cells (NSCs) injury, and explored the underlying molecular mechanism. Methods: Before NSCs were subjected to OGD/R treatment, NSCs were transfected with or without overexpressing cZNF292, si-cZNF292 or miR-22 inhibitor. Viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…In addition, three circRNAs (cZNF292, TLK1, and circ_008018) were significantly increased in the MCAO/R mouse model and mouse neurons under OGD/R and knockdown of the circRNAs attenuated neuronal injury during cerebral I/R. These effects were related to cell apoptosis mediated by targeting miR-22/Wnt/b-catenin (under OGD/R), miR-335-3p/TIPARP (under OGD/R and cerebral I/R), and miR-99a/Pi3k/Akt/GSK3b (cerebral I/R) [ 116 118 ]. Furthermore, the expression levels of circTLK1 in patients with AIS were notably increased in comparison with healthy controls.…”
Section: Lncrna/circrna-mirna-mrna Axis In Irimentioning
confidence: 99%
“…In addition, three circRNAs (cZNF292, TLK1, and circ_008018) were significantly increased in the MCAO/R mouse model and mouse neurons under OGD/R and knockdown of the circRNAs attenuated neuronal injury during cerebral I/R. These effects were related to cell apoptosis mediated by targeting miR-22/Wnt/b-catenin (under OGD/R), miR-335-3p/TIPARP (under OGD/R and cerebral I/R), and miR-99a/Pi3k/Akt/GSK3b (cerebral I/R) [ 116 118 ]. Furthermore, the expression levels of circTLK1 in patients with AIS were notably increased in comparison with healthy controls.…”
Section: Lncrna/circrna-mirna-mrna Axis In Irimentioning
confidence: 99%
“…Recent findings revealed that many circRNAs contribute to the regulation of NSCs function. For example, Cao et al demonstrated that silencing circRNA cZNF292 alleviates oxygen-glucose deprivation/reperfusion (OGD/R)-induced NSC injury, thus promoting the activation of protein kinase C/extracellular signal-regulated kinase and Wnt/β-catenin pathways by upregulating miR-22 [115]. In another study, it was observed that during the differentiation of NSCs, the expression of circHIPK2 was decreased, which played a neu-Downloaded from http://portlandpress.com/bioscirep/article-pdf/doi/10.1042/BSR20212510/926427/bsr-2021-2510.pdf by guest on 21 December 2021 roprotective role and facilitated nerve recovery after stroke.…”
Section: Circrnas In Neural Stem Cellsmentioning
confidence: 99%
“…Through the neural stem cells experiment of oxygen-glucose deprivation/reperfusion (OGD/R)-induced injury, cZNF292 was over-expressed and then ORD/R injury exacerbated. Instead, cZNF292 had negative influence on miR-22, after which the insult was getting better by the way of wnt/β-catenin pathway ( Figure 2A ) ( 80 ). This signaling has been evidenced in importance for the differentiation of neurons and the formation of neural circuits, which are likely to be relevant to the arrangement of cerebrovascular and BBB ( 81 ).…”
Section: Circrnas As Potential Biomarkers For Neurological Impairments and Diseasesmentioning
confidence: 99%